Depósito de calda sobre linhagem de milho aplicada por pulverização terrestre e aérea e por quimigação para o controle de Spodoptera frugiperda (Smith, 1797) (Lepidoptera: Noctuidae) - Nascimento, Ana Paula de Castro (2012)
Pesticides can be applied via aircraft, ground-sprayers or through sprinkler irrigation. However, selecting the best option is complicated by the limited number of studies comparing these techniques. Thus, we studied chlorpyrifos insecticide deposition applied via aircraft (30 l ha-1), tractor-mounted sprayer (200 l ha-1) and chemigation (70,000 l ha-1) for the control of Spodoptera frugiperda (J.E. Smith) in two corn populations (70,000 and 100,000 plants ha-1). Active ingredient residue on the leaves of the corn plants was evaluated by gas chromatography immediately after and ten days after treatment. Armyworm numbers in each plot and a control were also evaluated. Aerial and ground applications of chlorpyrifos led to greater active ingredient deposition than did chemigation. Neither plant population (70,000 and 100,000 plants ha-1) affected insecticide deposition. S. frugiperda control was similar for all three application methods. Chemigation, however, resulted in less deposition on the plants and consequently greater insecticide loss to the soil, which should be considered in assessing environmental impact.